Airborne Microplastics in indoor environments: current knowledge, methodological challenges, and future directions - Claudia Campanale; Leonardo Barlucchi; Augusta Piccardi; Jacopo La Nasa; Francesca Modugno; Marcello De Rossi; Lorenzo Palumbo (Building and Environment, 2026)

Water use of an irrigated peach orchard treated with different plastic mulching films under Mediterranean climate - Rossana Monica Ferrara; Maria Roberta Bruno; Sergio Ruggieri; Gabriele De Carolis; Pasquale Campi; Onofrio Cappelluti; Alessandro Ciurlia; Pietro Maggi; Anna Francesca Modugno; Alessandro Montaghi; Alessandro Azzolini; Valerio Minorenti; et al. (Irrigation Science, 2025)

Overview of regenerative and agroforestry-based cotton systems in the Mediterranean and beyond: a review - Mesele Negash; Yitagesu Tekle Tegegne; Marc Palahi; Ziantoni Valter; Simone Pietro Garofalo; Gabriele De Carolis; Pasquale Campi; Anna Francesca Modugno; Giuseppe Scarascia-Mugnozza (Agroforestry Systems, 2025)

The combination of hyperspectral imaging, untargeted metabolomics and lipidomics highlights a coordinated stress-related biochemical reprogramming triggered by polyethylene nanoparticles in lettuce - Leilei Zhang; Lori Hoagland; Yang Yang; Pier Paolo Becchi; Anatoly P. Sobolev; Giuseppe Scioli; Jacopo La Nasa; Greta Biale; Francesca Modugno; Luigi Lucini (Science of The Total Environment, 2025)

Abiotic degradation and accelerated ageing of microplastics from biodegradable and recycled materials in artificial seawater - Leonardo Barlucchi; Greta Biale; Jacopo La Nasa; Marco Mattonai; Stefano Pezzini; Andrea Corti; Valter Castelvetro; Francesca Modugno (Science of The Total Environment, 2024)

First insights of cotton intercropping with peach trees under Mediterranean conditions - Gabriele De Carolis; Simone Pietro Garofalo; Nicola Sanitate; Anna Francesca Modugno; Giuseppe Scarascia-Mugnozza; Marc Palahì; Mesele Negash Tesemma; Pasquale Campi (Agroforestry Systems, 2024)

Py–GC–MS analysis for microplastics: Unlocking matrix challenges and sample recovery when analyzing wastewater for polypropylene and polystyrene - Jeanette Lykkemark; Marco Mattonai; Alvise Vianello; Alessio Gomiero; Francesca Modugno; Jes Vollertsen (Water Research, 2024)

Plastic breath: Quantification of microplastics and polymer additives in airborne particles - Donatella Pomata; Jacopo La Nasa; Greta Biale; Leonardo Barlucchi; Alessio Ceccarini; Patrizia Di Filippo; Carmela Riccardi; Francesca Buiarelli; Francesca Modugno; Giulia Simonetti (Science of The Total Environment, 2024)

Effects of microplastics on microbial community dynamics in sediments from the Volturno River ecosystem, Italy - Maria Maisto; Maria Antonietta Ranauda; Daniela Zuzolo; Maria Tartaglia; Alessia Postiglione; Antonello Prigioniero; Alessandra Falzarano; Pierpaolo Scarano; Valter Castelvetro; Andrea Corti; Francesca Modugno; Jacopo La Nasa; et al. (Chemosphere, 2024)

Water use of a super high-density olive orchard submitted to regulated deficit irrigation in Mediterranean environment over three contrasted years - Rossana Monica Ferrara; Maria Roberta Bruno; Pasquale Campi; Salvatore Camposeo; Gabriele De Carolis; Liliana Gaeta; Nicola Martinelli; Marcello Mastrorilli; Anna Francesca Modugno; Teresa Mongelli; Mariagrazia Piarulli; Sergio Ruggieri; et al. (Irrigation Science, 2024)

Magic extraction: solid-phase extraction and analytical pyrolysis to study polycyclic aromatic hydrocarbon and polychlorinated biphenyls in freshwater - Jacopo La Nasa; Greta Biale; Francesca Modugno; Alessio Ceccarini; Stefania Giannarelli (Environmental Science and Pollution Research, 2022)
Polycyclic aromatic hydrocarbons and polychlorinated biphenyls are commonly categorized as persistent organic pollutants. In order to analyze these pollutants, customized stationary phases are increasingly being developed and synthesized for solid-phase extraction. In this work, we tested a new solventless solid-phase extraction approach based on the use of a Magic Chemisorber® (Frontier Lab) which consists of a bead-covered polydimethylsiloxane stationary phase with a thickness of 500 µm. These devices are directly immersed into aqueous samples and then introduced into a pyrolysis–gas chromatography-mass spectrometry system equipped with a cryofocusing system for the thermal desorption and analysis of the adsorbed species. Our new method performs better than the most recent solid-phase extraction devices, with limits of detection lower than 2.7 ng/L and limits of quantification lower than 9.0 ng/L. The method was tested on standard compounds and on an environmental sample, showing the potential to characterize other chemical species besides the persistent organic pollutants, such as phthalate plasticizers and antioxidants.

New methodologies for the detection, identification, and quantification of microplastics and their environmental degradation by-products - Valter Castelvetro; Andrea Corti; Greta Biale; Alessio Ceccarini; Ilaria Degano; Jacopo La Nasa; Tommaso Lomonaco; Antonella Manariti; Enrico Manco; Francesca Modugno; Virginia Vinciguerra (Environmental Science and Pollution Research, 2021)
Sampling, separation, detection, and characterization of microplastics (MPs) dispersed in natural water bodies and ecosystems is a challenging and critical issue for a better understanding of the hazards for the environment posed by such nearly ubiquitous and still largely unknown form of pollution. There is still the need for exhaustive, reliable, accurate, reasonably fast, and cost-efficient analytical protocols allowing the quantification not only of MPs but also of nanoplastics (NPs) and of the harmful molecular pollutants that may result from degrading plastics. Here a set of newly developed analytical protocols, integrated with specialized techniques such as pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS), for the accurate and selective determination of the polymers most commonly found as MPs polluting marine and freshwater sediments are presented. In addition, the results of an investigation on the low molecular weight volatile organic compounds (VOCs) released upon photo-oxidative degradation of microplastics highlight the important role of photoinduced fragmentation at a molecular level both as a potential source of hazardous chemicals and as accelerators of the overall degradation of floating or stranded plastic debris.

Aberrant functional connectivity in patients with Parkinson’s disease and freezing of gait: a within- and between-network analysis - Komal Bharti; Antonio Suppa; Sara Pietracupa; Neeraj Upadhyay; Costanza Giannì; Giorgio Leodori; Francesca Di Biasio; Nicola Modugno; Nikolaos Petsas; Giovanni Grillea; Alessandro Zampogna; Alfredo Berardelli; et al. (Brain Imaging and Behavior, 2020)

Olive mill wastewaters: quantitation of the phenolic content and profiling of elenolic acid derivatives using HPLC-DAD and HPLC/MS 2 with an embedded polar group stationary phase - Marco Mattonai; Andrea Vinci; Ilaria Degano; Erika Ribechini; Massimiliano Franceschi; Francesca Modugno (Natural Product Research, 2019)

Abnormal Cerebellar Connectivity Patterns in Patients with Parkinson’s Disease and Freezing of Gait - Komal Bharti; Antonio Suppa; Sara Pietracupa; Neeraj Upadhyay; Costanza Giannì; Giorgio Leodori; Francesca Di Biasio; Nicola Modugno; Nikolaos Petsas; Giovanni Grillea; Alessandro Zampogna; Alfredo Berardelli; et al. (The Cerebellum, 2019)

Anselm Kiefer: a study of his artistic materials - Giovanni Bartolozzi; Marcelo Picollo; Veronica Marchiafava; Silvia A. Centeno; Isabelle Duvernois; Francesca Di Girolamo; Francesca Modugno; Jacopo La Nasa; Maria Perla Colombini; Antonio Rava (Archaeological and Anthropological Sciences, 2016)

Feasibility of SRC Species for Growing in Mediterranean Conditions - Alejandra Navarro; Anna Maria Stellacci; Pasquale Campi; Carolina Vitti; Francesca Modugno; Marcello Mastrorilli (BioEnergy Research, 2016)

Identification of invasion specific splice variants of the cytoskeletal protein Mena present in mammary tumor cells during invasion in vivo - Sumanta Goswami; Ulrike Philippar; Daqian Sun; Antonia Patsialou; Jacob Avraham; Weigang Wang; Francesca Di Modugno; Paola Nistico; Frank B. Gertler; John S. Condeelis (Clinical & Experimental Metastasis, 2009)